Asset‐based poverty transition and persistence in rural China. (1st December 2016) - You, Jing
Abstract: This article tests empirically for transition and persistence of poverty in rural China based on the theory of asset‐based poverty traps. It proposes an analytical framework mitigating the problem of endogenous switching between accumulation regimes and disentangling the true state‐dependence of poverty. Specifically, a dynamic asset threshold separating households into downward and upward mobility regimes is identified after taking households' unobserved characteristics and observed regime‐differentiated accumulation strategies into account. The static analysis identifies causality running from settling into a downward mobility regime to the probability of poverty measured by consumption. Furthermore, allowing for endogenous initial poverty status, the dynamic analysis finds strong true state‐dependence in poverty. Households with the same characteristics are nearly twice as likely to be poor as if they had not previously switched to the accumulation regime. Assets below the dynamic threshold serve as a conduit through which poverty propagates itself. Factors that help to break this vicious circle are identified.